Semantics in Data and Knowledge Bases 4th International Workshops, SDKB 2010, Bordeaux, France, July 5, 2010, Revised Selected Papers - Schewe, Klaus-Dieter; Thalheim, Bernhard (Springer eBooks., 2011)
This book constitutes the thoroughly refereed post-proceedings of the 4th International Workshop on Semantics in Data and Knowledge Bases, SDKB 2010, held in Bordeaux, France in July 2010. The 6 revised full papers presented together with an introductory survey by the volume editors were carefully reviewed and selected during two rounds of revision and improvement. The papers reflect a variety of approaches to semantics in data and knowledge bases.